2021
DOI: 10.1016/j.bja.2021.06.004
|View full text |Cite|
|
Sign up to set email alerts
|

Association of the intraoperative peripheral perfusion index with postoperative morbidity and mortality in acute surgical patients: a retrospective observational multicentre cohort study

Abstract: Background: We hypothesised that in acute high-risk surgical patients, a lower intraoperative peripheral perfusion index (PPI) would indicate a higher risk of postoperative complications and mortality. Methods: This retrospective observational study included 1338 acute high-risk surgical patients from November 2017 until October 2018 at two University Hospitals in Denmark. Intraoperative PPI was the primary exposure variable and the primary outcome was severe postoperative complications defined as a ClavieneDi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…In a large recent and retrospective study, intraoperative PI was associated with severe postoperative complications or death (lower values being associated with worse outcomes) in a time-dependent manner even after adjustment for confounding variables [47]. Furthermore, they observed that the association between PI with the primary outcome was higher in patients with MAP > 65 mmHg compared to patients with MAP ≤ 65 mmHg (OR = 1.17; 95% CI 1.09-1.27; p < 0.001 vs. OR = 1.07; 95% CI 1.02-1.13; p = 0.011; respectively), suggesting a degree of incoherence between systemic haemodynamic and microcirculation.…”
Section: Pi and Prognosis In Anaesthesiamentioning
confidence: 98%
“…In a large recent and retrospective study, intraoperative PI was associated with severe postoperative complications or death (lower values being associated with worse outcomes) in a time-dependent manner even after adjustment for confounding variables [47]. Furthermore, they observed that the association between PI with the primary outcome was higher in patients with MAP > 65 mmHg compared to patients with MAP ≤ 65 mmHg (OR = 1.17; 95% CI 1.09-1.27; p < 0.001 vs. OR = 1.07; 95% CI 1.02-1.13; p = 0.011; respectively), suggesting a degree of incoherence between systemic haemodynamic and microcirculation.…”
Section: Pi and Prognosis In Anaesthesiamentioning
confidence: 98%
“…It is assumed that systemic hemodynamics – reflected by cardiac output or blood pressure – are coupled with microcirculatory tissue perfusion. The peripheral perfusion index is a photoplethysmography-derived microcirculatory tissue perfusion variable that has been associated with impaired outcome in surgical patients [ 23 , 24 ].…”
Section: Peripheral Perfusion Index Monitoringmentioning
confidence: 99%
“…These studies show the vast potential of measuring the peripheral perfusion index. A recent retrospective study further showed a strong correlation between impaired intraoperative peripheral perfusion index and postoperative outcomes [ 23 ]. With growing evidence showing the importance of the peripheral perfusion index, it will be interesting to see how photoplethysmography and the peripheral perfusion index can be integrated into hemodynamic monitoring and management.…”
Section: Peripheral Perfusion Index Monitoringmentioning
confidence: 99%
“…Peripheral perfusion index (PPI) is generated from the pulse oximetry signal, and changes in peripheral perfusion, both from reduced CO and sympathetically mediated peripheral vasoconstriction to augment central blood volume, are reflected in PPI 25 . In a recent study based on more than 1.000 acute high‐risk adult surgical patients, it was clearly shown that low PPI values during anesthesia are linked to a higher risk for severe postoperative complications and/or death 25 . Interestingly, no such correlation could be found with regard to low blood pressure (defined as MAP ≤65 mm Hg).…”
Section: Main Articlementioning
confidence: 99%